Living on the edge: studies on ecology of plant species and populations at the limits of their geographic range. Tribute to Professor Janusz B. Faliński (1934-2004) - Czarnecka, Bożenna (Biodiversity: Research and Conservation, 2015)
The studies on Senecio rivularis are an example of long-term ecological studies at the population level, conducted in the RNP since 1987, e.g., in terms of changes in the size structure of individuals compared to the changes in the surface area covered by this population. A nearly 3-fold increase in the area inhabited by the population was accompanied by changes in the spatial organisation of the population and individual size structure dynamics, which reflects the intensification of intra- and interspecific competition, and indicates condition changes in the population area.